2021
DOI: 10.1186/s12909-021-02896-1
|View full text |Cite
|
Sign up to set email alerts
|

Online teaching in physiotherapy education during COVID-19 pandemic in Italy: a retrospective case-control study on students’ satisfaction and performance

Abstract: Background During COVID-19 pandemic, physiotherapy lecturers faced the challenge of rapidly shifting from face-to-face to online education. This retrospective case-control study aims to compare students’ satisfaction and performances shown in an online course to a control group of students who underwent the same course delivered face-to-face in the previous five years. Methods Between March and April 2020, a class (n = 46) of entry-level physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0
17

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(114 citation statements)
references
References 22 publications
(28 reference statements)
4
80
0
17
Order By: Relevance
“…When the EPTEs perceived the teaching and learning process as an advantage theme of OT they declared that it was suitable mainly for online students’ assessment and none of them found it advantageous for clinical instructions. The positive perception of the EPTEs regarding the advantage of online students’ assessment is supported by the results of the study done by Rossettini et al in 2021 in which a comparison of Italian PT students’ performance in an oral exam for a case-based course between two groups of students (online and face-to-face) was for the advantage of the online group [ 26 ]. But it should be considered that the higher performance in the oral exam for the online group of students might not actually represent higher knowledge and ability to acquire this knowledge in a clinical scenario as claimed by the researchers.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…When the EPTEs perceived the teaching and learning process as an advantage theme of OT they declared that it was suitable mainly for online students’ assessment and none of them found it advantageous for clinical instructions. The positive perception of the EPTEs regarding the advantage of online students’ assessment is supported by the results of the study done by Rossettini et al in 2021 in which a comparison of Italian PT students’ performance in an oral exam for a case-based course between two groups of students (online and face-to-face) was for the advantage of the online group [ 26 ]. But it should be considered that the higher performance in the oral exam for the online group of students might not actually represent higher knowledge and ability to acquire this knowledge in a clinical scenario as claimed by the researchers.…”
Section: Discussionmentioning
confidence: 89%
“…Other studies [ 33 , 34 ] reported the insufficiency of interactive material as one of the barriers to OT, particularly websites. Students’ perceived satisfaction was different from that of the EPTEs, the Italian online and face-to-face two-group students [ 26 ] showed equal satisfaction with the case-based course introduced to the two groups. The difference in perception between EPTEs and the Italian PT students may be related to the difference between the case-based course and the clinical and practical courses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a course of scientific writing for healthcare students, including physiotherapist students, online instruction was better than standard face-to-face instruction in terms of writing quality [30]. Finally, a recent study produced during COVID-19 pandemic showed comparable students' performance and satisfaction after a course delivered online when compared to an historic cohort of students who underwent the same course face to face in previous years [31].…”
Section: Digital Educationmentioning
confidence: 96%
“…Some studies had indicated that virtual online sessions may increase student confidence in clinical decision making [ 3 ], increase students’ knowledge of other professional roles [ 4 ] and increase a student’s perception of team performance [ 5 ]. Since then, several studies have demonstrated the effectiveness of virtual learning with students achieving learning outcomes similar to in-person experiences [ 6 , 7 ], reporting online learning as a positive experience [ 8 , 9 ] and findings of higher student performance in online learning strategies compared to in-person learning, with no difference in student satisfaction [ 10 ].…”
Section: Introductionmentioning
confidence: 99%